Put the steps in order that are used to solve the following systems of equations by substitution.%0D%0A%0D%0A−7x−2y=−13%0D%0A−%0D%0A7%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0Ax−2y=11%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A11%0D%0A(10 points)%0D%0AArrange responses in the correct order to answer the question. Select a response, navigate to the desired position and insert response at that position. Responses can be selected and inserted using the space bar, enter key, left mouse button or touchpad. Responses can be moved using the up and down arrow keys or by dragging with a mouse.%0D%0A%0D%0A−7(2y+11)−2y=−13%0D%0A−%0D%0A7%0D%0A(%0D%0A2%0D%0A%0D%0A+%0D%0A11%0D%0A)%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0A−14y−77−2y=−13%0D%0A−%0D%0A14%0D%0A%0D%0A−%0D%0A77%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0Ax=3%0D%0A%0D%0A=%0D%0A3%0D%0A%0D%0Ax−2y=11%0D%0A%0D%0A−%0D%0A2%0D%0A%0D%0A=%0D%0A11%0D%0A --> x=2y+11%0D%0A%0D%0A=%0D%0A2%0D%0A%0D%0A+%0D%0A11%0D%0A%0D%0Ay=−4%0D%0A%0D%0A=%0D%0A−%0D%0A4%0D%0A%0D%0Ax+8=11%0D%0A%0D%0A+%0D%0A8%0D%0A=%0D%0A11%0D%0A%0D%0Ax−2(−4)=11%0D%0A%0D%0A−%0D%0A2%0D%0A(%0D%0A−%0D%0A4%0D%0A)%0D%0A=%0D%0A11%0D%0A%0D%0A−16y−77=−13%0D%0A−%0D%0A16%0D%0A%0D%0A−%0D%0A77%0D%0A=%0D%0A−%0D%0A13%0D%0A%0D%0A−16y=64%0D%0A−%0D%0A16%0D%0A%0D%0A=%0D%0A64%0D%0A%0D%0A(3,−4)%0D%0A(%0D%0A3%0D%0A,%0D%0A−%0D%0A4%0D%0A)

1 answer

1. Solve one of the equations for one of the variables (in this case, solve the first equation for x: x = 2y + 11).
2. Substitute the expression for that variable into the other equation (replace x in the second equation with 2y + 11).
3. Simplify the equation by performing any necessary operations (in this case, distribute the -2 to each term inside the parentheses).
4. Solve the resulting equation for the remaining variable (in this case, solve for y: -16y - 77 = -13).
5. Substitute the value of y back into the expression for x (replace y in x = 2y + 11 with -4).
6. Simplify the expression for x to get the final solution (in this case, x = 3).
7. Write the final solution as the ordered pair (x, y) (in this case, (3, -4)).